Solar energy policy: Malaysia vs developed countries - Fayaz, H.; Rahim, N.A.; Saidur, Rahman; Solangi, K.H.; Niaz, H.; Hossain, M.S. (2011)
Countries all over the world is enquiring and taking efforts to implement the environment friendly renewable energy to mitigate the negative impacts of fossil fuels on the environment and their fast depletion. To reduce the reliance on fossil fuels and environmental degradation, many countries have focused and formulated solar energy related policies to increase its share into energy mix. In this paper a review of the solar energy policies, implemented in the developed countries and Malaysia, are discussed as well as the discussion of successful existing solar energy policies in the developed countries. According to the 2010 BP Statistical Energy Survey, the world cumulative installed solar energy capacity was 22928.9 MW in 2009, a change of 46.9 compared to 2008. After the review of literature, FiT, RPS and Incentives are found to be the most beneficial energy policies implemented by the developed countries. These policies create the paths to promote the development and implementation of renewable energy technologies. Also, the current policies related to solar energy in Malaysia are investigated and compared with developed countries.